Using a morphological chart to develop fashion products from recycled knit waste (ModaPalavra e-periódico, 2020)
Thisarticleaimstoinvestigateandexperimentenvironmentallysustainablesolutionsusingcottonknitwasteandhandknittingtodevelopnewfashionproducts.Theknowwastecamefromimperfectknitfabricsdiscardedbyfabricindustriesandcircularknitgarmentsdiscardedbyconsumers.Thetoolusedasacreativemeanofdevelopmentwasthemorphologicalchart,whichallowedapproximatelyonehundredandfiftyideasofgarmentstobegenerated.Fiveideaswereidentifiedasmainproductconcept.Aprototypeofavestwasmadetotesttheviabilityoftheuseofthemorphologicalchartdodevelopacreativefashionproduct.Thereproducibilityofthemethodologywassuccessfullytestedbyhandcraftartiststhatworkwithhandknitting
Keywords: morphological chart; recycled; fashion